Macedonia - Alexandria - Gorzelany, Dorota (Archaeopress, 2019)
This book explores the influence of Macedonians and Greeks settling in Alexandria ad Aegyptum on the structural form of underground tombs, comparing in synthetic form the structural elements of the cist graves, chamber and rock-cut tombs of Macedonia with the Alexandrian hypogea, while taking into account geographical factors that conditioned them.